SAT0154 Effectiveness and safety of CT-P13 in patients with rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis and plaque psoriasis: observational study in republic of korea. (15th June 2017) - Kim, D-W; Kim, T-H; Kwon, SR; Lee, EY; Son, C-N; Kim, YS; Kim, SH; Park, Y-B; Hur, J-W; Lee, H-S; Lee, SJ; Lee, SH
Abstract : Background: CT-P13 is approved as a biosimilar of innovator infliximab for marketing in 79 countries around the world. After approval, observational study has been conducted in Republic of Korea in patients with Rheumatoid Arthritis (RA), Ankylosing Spondylitis (AS), Psoriatic Arthritis (PsA) and Plaque Psoriasis (PS). Objectives: To evaluate the effectiveness and safety of CT-P13 under routine care in Republic of Korea. Methods: This observational study included both biologic naïve patients (Naïve group) and patients who switched from other anti-tumor necrosis factor (TNF)s to CT-P13 (Switch group). Effectiveness were evaluated based on remission (DAS28≤2.6 in RA, BASDAI<3 in AS and absence of swollen and tender joint counts in PsA), and response (BASDAI 20/50/70 in AS and PASI 50/75 in PS). Adverse events (AEs) were collected over 6 month period. Results: Total 940 patients (400 with RA, 531 with AS, 3 with PsA and 6 with PS) were registered and 338 (36.0%) patients (108 with RA, 228 with AS, 2 with PS) who switched to CT-P13 were included. The proportion of patients achieving remission was similar between Naïve and Switch groups in both RA and AS during post-baseline visits (Table 1 ). In RA, the proportion of patients achieving each disease activity category by DAS28 was similar between Naïve and Switch groups (Figure 1 ). The proportion of patients who achieved BASDAI 20/50/70 response gradually increased from week 6 to week 24 or 30 in Naïve group with AS (Figure 1 ). Fifty percent of naïve patients with PsA achieved clinical remission. The proportions of both PASI 50 and 75 responses were 50% at Week 22 in Naïve group and were 100% and 50% in Switch group, respectively during post-baseline visits in PS patients. Throughout this study, treatment-emergent adverse events (TEAE) and treatment-emergent serious adverse events (TESAE) were reported as Table 2 . Only 11% of patients experienced infection. Conclusions: CT-P13 is efficacious and well-tolerated in RA/AS/PsA/PS patients. Efficacy and safety results in patients treated with CT-P13 were clinically consistent to historical data [1, 2, 3]. Especially, Switch group results showed that CT-P13 provides a useful alternative to other anti-TNFs. References: Kobayashi et al (2016). Hetland et al (2005). Hetland et al (2010). Disclosure of Interest: D.-W. Kim: None declared, T.-H. Kim: None declared, S. R. Kwon: None declared, E. Y. Lee: None declared, C.-N. Son: None declared, Y. S. Kim: None declared, S. H. Kim: None declared, Y.-B. Park: None declared, J.-W. Hur: None declared, H.-S. Lee: None declared, S. J. Lee Employee of: CELLTRION, Inc., S. H. Lee Employee of: CELLTRION, Inc.